PENDUGAAN UMUR SIMPAN COOKIES NENAS DENGAN METODE AKSELERASI BERDASARKAN PENDEKATAN KADAR AIR KRITIS (The Estimation Of Shelf Life Of Pineapple Cookies Using Accelerated Method Based On Critical Moisture Content Approach) - Citra Pertiwi; Sentosa Ginting; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2017)
ABSTRACT The aim of this research was to determine the effect of type of packaging and storage time on the quality of pineapple cookies and to estimate the shelf life of pineapple cookies that were packaged in Oriented Polypropylene, Polyethylene, and Metalized Plastic. The effect of type of packaging and storage time of the pineapple cookies was using factorial Completely Randomized Design with two factors, i. e: the types of packaging (K) (Oriented Polypropylene (OPP), Polyethylene (PE), Metalized Plastic (MP)) and storage time (L)(7 days, 14 days, 21 days). Each treatment was keeped in the room temperature and 15 oC. The analyzed parameter were moisture content, fat content, free fatty acids, and organoleptic value of colour, aromatic, taste and texture. Estimation of shelf liife pineapple cookies was using accelerated method based on critical moisture content approach. The results showed that the type of packaging had highly significant effect on water content, fat content, free fatty acids, organoleptic value (aromatic and texture) in the room temperature and 15 oC . Storage time had highly significant effect on water content, fat content, free fatty acids, organoleptic value (aromatic and texture) in the room temperature and 15 oC. The Interaction between the type of packaging and storage time had significant effect on water content in the room temperature and 15 oC. The shelf life estimation of pineapple cookies in the room temperature was 97 days for OPP, 9 days for PE and 400 days for metalized plastic. The shelf life estimation of pineapple cookies in the 15 oC was 509 days for OPP, 47 days for PE and 2091 days for metalized plastic. Keywords: pineapple cookies, shelf life, storage time, type of packaging ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh jenis kemasan dan lama penyimpanan terhadap mutu cookies nenas, dan untuk menduga umur simpan dari cookies nenas yang dikemas dalam kemasan Oriented Polypropylene, Polietilen, dan Metalized Plastic. Pengaruh jenis kemasan dan lama penyimpanan terhadap cookies nenas menggunakan rancangan acak lengkap (RAL) dengan 2 faktor yaitu jenis kemasan (K) (Oriented Polypropylene (OPP), Polietilen (PE), Metalized Plastic (MP)) dan lama penyimpanan (L) (7 hari, 14 hari, dan 21 hari). Masing-masing perlakuan disimpan pada suhu ruang dan suhu 15 oC. Parameter yang dianalisa adalah kadar air, kadar lemak, kadar asam lemak bebas, nilai organoleptik warna, aroma, rasa dan tekstur. Pendugaan umur simpan cookies nenas menggunakan metode akselerasi berdasarkan pendekatan kadar air kritis. Hasil penelitian menunjukkan bahwa jenis kemasan memberikan pengaruh berbeda sangat nyata terhadap kadar air, asam lemak bebas, nilai organoleptik (aroma dan tekstur) pada suhu ruang dan suhu 15 oC. Lama penyimpanan memberikan pengaruh berbeda sangat nyata terhadap kadar air, asam lemak bebas, nilai organoleptik (aroma dan tekstur) pada suhu ruang dan suhu 15 oC. Interaksi antara jenis kemasan dan lama penyimpanan memberikan pengaruh berbeda nyata terhadap kadar air pada suhu ruang dan suhu 15 oC. Umur simpan cookies nenas yang disimpan pada suhu ruang pada berbagai jenis kemasan yaitu 97 hari untuk kemasan OPP, 9 hari untuk kemasan PE, dan 400 hari untuk kemasan Metalized Plastic. Sedangan umur simpan cookies nenas yang disimpan pada suhu showcase (15 oC) pada berbagai jenis kemasan yaitu 509 hari untuk kemasan OPP, 47 hari untuk kemasan PE, dan 2091 hari untuk kemasan Metalized Plastic. Kata kunci : cookies nenas, jenis kemasan, lama penyimpanan, umur simpan